Analysis of the effects of operator experience and learning in laser sintering. (19th November 2021) - Alogla, Ageel; Baumers, Martin; Tuck, Christopher
Recent research into the cost performance of various additive manufacturing (AM) processes indicates that one important barrier is the extent of manual labour inputs required by the process. To explore this aspect, this study focuses on the experimental measurement of the AM operator time and improvement in operator effectiveness due to learning. Learning is assessed in two ways: First, this paper measures the reduction of labour time resulting through operator learning within a series of build repetitions and estimates a progress ratio capturing the learning effect within this series. Second, this paper assesses the impact of overall operator experience by comparing the labour time required by a novice operator and an expert operator. The results suggest that AM exhibits a learning effect for both the novice and the expert operator with progress ratios of 67.73% and 80.42% respectively contrasted with 80% for other manufacturing technologies. These results will inform new theorising on AM cost-quantity behaviour.